Effects of gelling bath on the physical properties of alginate gel beads and the biological characteristics of entrapped HepG2 cells. (29th August 2017) - Sun, Dongsheng; Liu, Yang; Wu, Hao; Ren, Ying; Ma, Xiaojun; Wu, Huijian; Sun, Guangwei
Abstract: Optimizing alginate gel beads is necessary to support the survival, proliferation, and function of entrapped hepatocytes. In this study, gelling bath was modified by decreasing calcium ion concentration and increasing sodium ion concentration. Alginate gel beads (using 36% G sodium alginate) prepared in the modified gelling bath had more homogeneous structure and better mass transfer properties compared with the traditional gelling bath that contains only calcium ions. Moreover, alginate gel beads generated in the modified gelling bath could significantly promote the HepG2 cell proliferation and the growth of cell spheroids, and maintain the albumin secretion ability similar to alginate gel beads prepared in the traditional gelling bath with only calcium ions. The mass transfer properties and cell proliferation were similar in ALG beads with different M/G ratio (36% G and 55% G) generated in the modified gelling bath, whereas they were significantly increased compared with alginate gel beads (55% G) in traditional gelling bath. These results indicated that adjusting the gelling bath was a simple and convenient method to enhance the mass transfer properties of alginate gel beads for 3D hepatocyte culture, which might provide more hepatocytes for the bioartificial liver support system.